The integration of knowledge in the work of Jacques Maritain (Teología, 2019)
The second part of this study develops the question of the unity of knowledge,under two aspects: the unity of order, which arises from the natural hierarchyof the sciences due to their distinct formal objects, and the unity of integration,which establishes the interaction between the disciplines in reference to the onematerial object. As to the unity of order the classical theory of subalternationis developed, with the distinctions called for by the actual diversification bothin the natural and human sciences. With regard to the unity of integration, the fundamental terms of the dialogue between philosophy, theology and science are presented. Finally, the original contribution of Maritain, which he called existential epistemology, is introduced, in which an attempt is made to overcome the rigidity of the formal objects towards an outlook directed to the concrete. As examples, the theme of knowledge as connatural, science as a virtue and the question of christian philosophy are introduced.
Keywords: Integration of Knowledge; Maritain; Science; Christian Philosophy